What We Know about the Public’s Level of Concern for Farm Animal Welfare in Food Production in Developed Countries - Cornish, Amelia (Animals (Basel), 2016)
SIMPLE SUMMARY: The production of food from animals poses many ethical challenges. This review explores what we know about different levels of concern for animal welfare in food production by such stakeholders as veterinarians, farmers, and the general public. Despite the general public’s level of concern for animal welfare in food production being high, their understanding and knowledge is poor. Thus, it is suggested that through widespread consciousness raising we can encourage the public to accurately translate their concerns into market drivers, in turn improving the welfare of billions of animals. ABSTRACT: Population growth and rising consumption of meat, dairy, eggs and fish are forcing the world to face the intersecting challenges of how to sustainably feed a population expected to exceed 9 billion by 2050, while also controlling the impact of food production on the planet, on people and on animals. This review acknowledges the absence of a globally accepted definition of animal welfare and then explores the literature regarding different levels of concern for animal welfare in food production by such stakeholders as veterinarians, farmers, and the general public. It focuses on the evidence that the general public’s level of concern for animal welfare is linked to various demographic and personal characteristics, such as age, gender, religion, location, meat eating, and knowledge of animal welfare. Certain animals have characteristics that influence concern for their welfare, with those species that are considered more intelligent being afforded more concern. There is compelling evidence that the general public’s understanding of animal welfare in food production is poor. Acknowledging that public concern can be a driving force to change current production methods, the authors suggest widespread consciousness raising to redefine socially acceptable methods of food production from animals and to ensure that it remains in step with societal concerns.